BUDAYA PADA TRADISI WETONAN DALAM STABILITAS SOSIAL DAN GENERASI MILENIAL DI DESA PANCAMUKTI - Modh Aji Isnaini; Irpinsyah Irpinsyah (Journal of Innovative and Creativity, 2025)
This study aims to find out how culture in the wetonan tradition plays a role in maintaining social stability in Pancamukti Village. And to find out the understanding of the millennial generation in Pancamukti Village about culture in the wetonan tradition. The method used in this study is a qualitative method, using a descriptive approach. Data collection techniques in this study use observation, interview and documentation techniques. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the study show that the wetonan tradition in Pancamukti Village has an important role in maintaining social stability by instilling noble values ​​such as mutual respect, mutual help, and mutual cooperation in the younger generation. And the understanding of the millennial generation in Pancamukti Village about the wetonan culture shows that despite the challenges of the development of the times and globalization, this tradition is still considered important as a cultural heritage. The millennial generation sees wetonan not just as a ritual, but as a means to understand their cultural identity and appreciate existing values